2020
DOI: 10.1038/s41598-020-59799-2
|View full text |Cite
|
Sign up to set email alerts
|

Intra-islet GLP-1, but not CCK, is necessary for β-cell function in mouse and human islets

Abstract: Glucagon-like peptide 1 (GLP-1) and cholecystokinin (CCK) are gut-derived peptide hormones known to play important roles in the regulation of gastrointestinal motility and secretion, appetite, and food intake. We have previously demonstrated that both GLP-1 and CCK are produced in the endocrine pancreas of obese mice. Interestingly, while GLP-1 is well known to stimulate insulin secretion by the pancreatic β-cells, direct evidence of CCK promoting insulin release in human islets remains to be determined. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 55 publications
(91 reference statements)
1
31
0
Order By: Relevance
“…In another study, SKIP-deficient mice improved glucose tolerance by increasing insulin and GLP-1 secretion [ 92 ], which suggests that SKIP deficiency in mice allow SphK1 to better regulate glucose tolerance. However, it remains to be established whether SKIP is acting only at the level of intestinal L cells or on the pancreatic β cell since it is already known that islet-derived GLP-1 is necessary for glucose-stimulated insulin secretion [ 93 ]. Not surprisingly, a consensus on the role of the SphK1/S1P axis in β-cells has not been reached.…”
Section: S1p Metabolism and Pancreatic β Cell Fatementioning
confidence: 99%
“…In another study, SKIP-deficient mice improved glucose tolerance by increasing insulin and GLP-1 secretion [ 92 ], which suggests that SKIP deficiency in mice allow SphK1 to better regulate glucose tolerance. However, it remains to be established whether SKIP is acting only at the level of intestinal L cells or on the pancreatic β cell since it is already known that islet-derived GLP-1 is necessary for glucose-stimulated insulin secretion [ 93 ]. Not surprisingly, a consensus on the role of the SphK1/S1P axis in β-cells has not been reached.…”
Section: S1p Metabolism and Pancreatic β Cell Fatementioning
confidence: 99%
“…In a study using non-diabetic C57BL/6 J mice, researchers identified a subpopulation of GLP-1 expressing alpha cells in dispersed islets. 40 As these studies used isolated primary islet samples, it has been suggested that islet-isolation and culturing may cause sufficient islet stress to induce GLP-1. This stress-induced GLP-1 production may be a potential mechanism to prevent further islet cell damage.…”
Section: Evidence For Glp-1 Expression In Rodent Isletsmentioning
confidence: 99%
“…In a study using non-diabetic C57BL/6 J mice, researchers identified a subpopulation of GLP-1 expressing alpha cells in dispersed islets. 40 …”
Section: Evidence For Glp-1 Expression In Rodent Isletsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is classically known to be mediated by glucagon signaling ( 10 ), which activates human β-cell G protein-coupled receptors (GPCR) of class B, including glucagon receptor (GCGR), and glucagon-like peptide 1 receptor (GLP-1R), promoting insulin secretion by an increase in cyclic AMP and the recruitment of insulin granules ( 50 ). However, GLP-1 is also secreted by human α-cells ( 52 54 ) and necessary for insulin secretion in human islets, as GLP-1R antagonism blunted glucose stimulated insulin secretion (GSIS) in vitro ( 54 ). Moreover, GLP-1 can elicit synchronous intracellular calcium oscillations in human whole islets ( 55 ), suggesting an important role of this hormone and the location of α-cells within the islet to obtain pulsatile and synchronized insulin secretion.…”
Section: Human Islet Architecture Favors Heterologous Contacts Betweementioning
confidence: 99%